Development of a Meal Support Device for Functional Recovery Using EMG Signals - Norihiko Saga; Reina Umeki; Naoki Saito; Jun-Ya Nagase; Toshiyuki Satoh (IEEE Access, 2020)
This paper describes a device to support a patient's motion of their upper limbs. The device has three functions in a single system: power assistance, rehabilitation, and meal support. The former two functions have been described in a previous study. In this paper, designs and evaluations of the meal supporting function considering maintaining residual muscular strength are presented. The mechanical design is based on human body statistical data. The controller consists of an electromyogram signal-based interface used for maintaining muscular strength. We evaluate the effectiveness of the meal supporting mode through some experimentation.